2014
DOI: 10.1074/jbc.m114.588541
|View full text |Cite
|
Sign up to set email alerts
|

Glycomic Characterization of Respiratory Tract Tissues of Ferrets

Abstract: Background: The ferret is a key animal model to study the transmission characteristics of influenza viruses.Results: Characterization of ferret respiratory tract tissues identified influenza virus glycan receptors.Conclusion: Species-specific influenza virus glycan receptors were identified.Significance: Our findings provide new insights into the usefulness of ferrets in the study of influenza virus infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(65 citation statements)
references
References 43 publications
1
64
0
Order By: Relevance
“…Although glycomics profiling of an airway epithelial cell line (Chandrasekaran et al, 2008), human and ferret respiratory lung tissues (Jia et al, 2014; Walther et al, 2013), and swine respiratory epithelium (Bateman et al, 2010), suggest the presence of extended branched N-glycans similar to those studied here, definitive analysis of human airway epithelium and, in particular, different sections of the airway, still remain to be carried out. A recent report suggesting that the soft palate of ferrets plays a prominent role in selection of HA mutations that promote a switch from avian-type to human-type receptor specificity (Lakdawala et al, 2015), emphasizes how potential variation in the expression of receptor glycans in different regions of the upper airway could account for selection of viruses with specificity for extended, human-type receptors.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Although glycomics profiling of an airway epithelial cell line (Chandrasekaran et al, 2008), human and ferret respiratory lung tissues (Jia et al, 2014; Walther et al, 2013), and swine respiratory epithelium (Bateman et al, 2010), suggest the presence of extended branched N-glycans similar to those studied here, definitive analysis of human airway epithelium and, in particular, different sections of the airway, still remain to be carried out. A recent report suggesting that the soft palate of ferrets plays a prominent role in selection of HA mutations that promote a switch from avian-type to human-type receptor specificity (Lakdawala et al, 2015), emphasizes how potential variation in the expression of receptor glycans in different regions of the upper airway could account for selection of viruses with specificity for extended, human-type receptors.…”
Section: Discussionmentioning
confidence: 76%
“…Thus, these terms belie the true complexity of the glycome and the potential for other aspects of glycan structure to be an important factor in receptor recognition. Glycan profiling of a human airway epithelial cell line (Chandrasekaran et al, 2008), human and ferret respiratory tract tissues (Jia et al, 2014; Walther et al, 2013), and porcine airway epithelial cells (Bateman et al, 2010) has revealed the presence of Asn-linked glycans (N-glycans) with extended branches as a unique characteristic of the airway glycome. While the branches of N-glycans on most cell types extend from the mannose core (Man 3 GlcNAc 2 Asn) by a single LacNAc (Galβ1-4GlcNAc) sequence, N-glycans in airway tissues exhibit extensions with multiple LacNAc repeats.…”
Section: Introductionmentioning
confidence: 99%
“…This is significant as ferrets are widely used to study influenza virus infection and transmission as the expression and distribution of sialic acids in the ferret respiratory tract is similar to humans, although not identical (Jia et al, 2014; van Riel et al, 2006). Neu5Gc may act as a decoy receptor for influenza viruses rather than a functional receptor, as shown using a Neu5Gc-expressing human lung cell line.…”
Section: Influenza Virusesmentioning
confidence: 99%
“…However, several differences between the ferret and human respiratory tract have been identified which could influence the outcome of infection. For example, the presence of Sda epitopes that carry ␣-2,3-NeuAc in the ferret respiratory tract is hypothesized to reduce potential binding sites for avian influenza viruses (43,44). The HA of H5Nx viruses possess the key residues Gln226 and Gly228 (H3 numbering) required for 2,3-linked sialic acid binding, indicating the virus has not adapted toward human-type receptor specificity.…”
Section: Figmentioning
confidence: 99%